Peran Mekanisme Tata Kelola Perusahaan Sebagai Variabel Moderasi Praktik Koneksi Politik Terhadap Agresivitas Pajak - Saraswati, Ade Maya (Universitas Winaya Mukti, 2024)
Tax targets that were not achieved were caused by actions to manage the tax burden by corporate taxpayers. One strategy is to minimize the tax burden in a legal way. This study aims to examine the moderating effect of corporate governance on political connections and tax aggressiveness. The research sample was 77 using purposive sampling technique. The analysis technique uses Eviews. Data processing using multiple regression and moderation regression. The results showed that political connections had no effect on tax aggressiveness, corporate governance had no effect on tax aggressiveness and the moderating effect of corporate governance did not moderate political connections on tax aggressiveness. Company management can pay attention to additional factors that may have a greater impact on tax policy and regulators may consider strengthening supervision or more specific policies to ensure effective corporate governance in managing taxes.